Авторські лексичні новотвори як джерело поповнення словникового складу мови - Гаврилюк, Н. (Лексикографічний бюлетень, 2012)
The author’s vocabulary neoplasms as a source of replenishment vocabulary are considered in the article. Examples of author’s nominations that have entered the common vocabulary are demonstrated. The individual authors growths found in the poetic language of ten and more authors, but not recorded in modern lexicographical works, are presented.